Unpacking b corps’ impact on sustainable development. An analysis from structuration theory - Tabares, Sabrina; Morales, Andrés; Calvo, Sara; Molina Moreno, Valentín (MDPI, 2022)
With Our Common Future and the United Nation’s global call to implement the Sustainable Development Goals (SDGs) in 2030, public policies increasingly emphasise the need for various actors to contribute to a global transformation and a more sustainable future. Despite growing research on hybrid organisations and their contributions to sustainable development, their impact on accelerating this transition might be faulty. Looking at a type of hybrid organisation, Certified B Corporations (B Corps), this article draws on a multiple case study of nine B Corps in a developing country in Latin America, Colombia. The study builds on the Structuration Theory to examine to what extent and how B Corps impact sustainable development. The article empirically shows that B Corps focus on four categories of sustainable development: considering future generations; enhancing human development; encouraging new mindsets, behaviours, and lifestyles; and promoting socio-political engagement. The findings suggest that B Corps develop communicative and narrative discourses and symbolic schemas as means of signification and follow norms and moral rules to exert legitimation and utilise authoritative resources to exercise power. The article contributes to research on hybrid organisations, sustainability transitions, and business models.
Keywords: B Corps; business models; hybrid organisations; structuration theory (ST); sustainability transitions; sustainable development (SD); triple bottom line (TBL); Scopus; JCR